2 Narratives of Covid: Loss, Dying, Death and Grief during COVID-19. (14th March 2023) - Mallon, Sharon; Borgstrom, Erica
Abstract : Introduction: The COVID-19 pandemic has impacted people's personal and professional lives, with many people experiencing various forms of loss including bereavement. The Open University (OU) is a large organisation with many students and staff impacted by the pandemic. The Open Thanatology group at the university noted a gap within the institution to collectively understand and support each other during this time. We sought to provide a space within the OU where students, staff and alumni could share stories and experiences of loss during the first year of the pandemic through narrative writing. Methods: People were invited to submit a narrative of up to 1, 500 words to the editors by early March 2021. The editors worked with authors to refine each contribution and self-published the collection in September 2021. Results: Over 30 authors contributed with a range of materials from personal essays, reflections on frontline work or research, and poetry. Topics included: loss during COVID-19; impossible choices and restricted presence during COVID-19; death and dying during the pandemic; death as a result of COVID-19; grief, loss and funerals during COVID-19; other experiences of grief during COVID-19. Contributors commented that the process was therapeutic and that it recognised and honoured their experiences. For some it was their first-time publishing. It captures a 'moment in time' and the difficulties people faced. Conclusion: Publishing the Narratives of Covid book has been a useful way of bringing people together within the Open University and connecting with and sharing people's experiences of death, loss and grief during the pandemic. Subsequent events at libraries have broaden the conversations beyond the university. Since the book is available as a free download, it has been used in education, research, reading groups, and public engagement. Book reference: Borgstrom, E. and Mallon, S. (2021) Narratives of Covid: Loss, Dying, Death and Grief During Covid-19. The Open University. https://oro.open.ac.uk/79260/